The PGPR Stenotrophomonas maltophilia SBP-9 Augments Resistance against Biotic and Abiotic Stress in Wheat Plants - Singh, Rajnish P.; Jha, Prabhat N. (Frontiers in Microbiology, 2017)
Certain plant growth promoting bacteria has ability to ameliorate abiotic and/or biotic stressors which can be exploited to enhance plant growth and productivity of the plants under stress conditions. Therefore, the present study aimed to examine the role of a rhizospheric bacterial isolate SBP-9 isolated from Sorghum bicolor (i) in promoting the wheat plant growth under salinity stress, and (ii) in enhancing the defense response in wheat against fungal pathogen ‘Fusarium graminearum’. The test isolate possessed plant growth promoting (PGP) traits including ACC deaminase (ACCD), gibberellic acid, indole acetic acid (IAA), siderophore, and inorganic phosphate solubilization. Under salt (NaCl) stress, inoculation of this isolate to wheat plant significantly increased plant growth in terms of various growth parameters such as shoot length/root length (20 to 39%), fresh weight/dry weight (28 to 42%), and chlorophyll content (24 to 56%) following inoculation of test isolate SBP-9. Bacterial inoculation decreased the level of proline, and malondialdehyde, whereas elevated the antioxidative enzymatic activities of superoxide-dismutase (SOD; 28 to 41%), catalase (CAT; 24 to 56%), and peroxidase (POX; 26 to 44%). Furthermore, it also significantly decreased the Na+ accumulation in both shoot and roots in the range of 25 to 32%, and increased the K+ uptake by 20 to 28%, thereby favoring the K+/Na+ ratio. On the other hand, the test isolate also enhanced the level of defense enzymes like β-1, 3 glucanase, phenylalanine ammonia lyase (PAL), peroxidae (PO), and polyphenol oxidase (PPO), which can protect plants from the infection of pathogens. The result of colonization test showed an ability of the test isolate to successfully colonize the wheat plants. These results indicate that Stenotrophomonas maltophilia SBP-9 has potential to promote the wheat growth under biotic and abiotic (salt) stressors directly or indirectly and can be further tested at field level for further exploitation as bioinoculant.